2020
DOI: 10.1002/pbc.28269
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐pregnancy obesity and childhood malignancies: A population‐based cohort study

Abstract: Condensation:The association between pre-pregnancy obesity and long-term risk for childhood malignancy. AbstractObjective: Exploring the effect of maternal obesity during pregnancy on the long-term health of offspring is of great importance. The aim of this study was to evaluate the association between maternal pre-pregnancy obesity and future risk of childhood malignancies. Study design:A population-based cohort analysis comparing the risk for long-term childhood malignancies (up to the age of 18 years) in ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Nine studies provided eligible prepregnancy BMI data ( Supplementary Table 1 , available online) ( 29-37 ). An additional 7 studies with maternal prepregnancy weight data were found but excluded because of vague obesity definitions/lack of ascertainment description ( 38 , 39 ), providing weight rather than BMI ( 40-42 ), or expressing BMI in categories that could not be converted into usable data ( 43 , 44 ). Eligible studies covered 3 404 747 participants and 14 706 childhood cancer patients across 5 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies provided eligible prepregnancy BMI data ( Supplementary Table 1 , available online) ( 29-37 ). An additional 7 studies with maternal prepregnancy weight data were found but excluded because of vague obesity definitions/lack of ascertainment description ( 38 , 39 ), providing weight rather than BMI ( 40-42 ), or expressing BMI in categories that could not be converted into usable data ( 43 , 44 ). Eligible studies covered 3 404 747 participants and 14 706 childhood cancer patients across 5 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a review of the full texts of 112 studies, 90 studies were excluded, mainly because they were reviews, nondescendant cancers, lack of information on maternal BMI or GWG, unclear or incomplete data, or duplicated data. Finally, twenty-two studies were identified as eligible and included in the present meta-analysis ( Figure 1 ) [ 13 , 14 , 15 , 16 , 20 , 21 , 22 , 23 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“… Forest plot of the association between maternal BMI and the risk of total cancer in offspring [ 13 , 14 , 15 , 16 , 20 , 21 , 22 , 23 , 33 , 34 , 35 , 36 , 38 , 39 , 40 , 42 , 43 , 44 , 45 , 46 ]. …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations